Factors influencing mask-wearing behavior in the context of COVID-19 severity risks in the post-COVID-19 era: a Japanese Nationwide Epidemiological Survey in 2023 - Shingo Noguchi; Tomohiro Ishimaru; Kazuhiro Yatera; Yoshihisa Fujino; Masayoshi Zaitsu; Takahiro Tabuchi (Environmental Health and Preventive Medicine)
Background: Although the global COVID-19 mortality rate is decreasing, COVID-19 remains an infectious disease with a high mortality rate, especially in older adults and individuals with comorbidities. In Japan, mask-wearing has been left to individual discretion since March 13, 2023, but remains a key protective measure. This study aimed to identify factors influencing individual mask-wearing behavior in post COVID-19 era, with a focus on risk factors for severe COVID-19. Methods: Data from 33,000 participants, obtained from the Japan COVID-19 and Society Internet Survey 2023, were used, which was conducted from September 25 to November 17, 2023. Participants were randomly selected from approximately 2.2 million panelists from a nationwide Japanese Internet research company, with sampling adjusted by age, sex, and living area to match the population distribution in Japan. The association between wearing a mask and risk factors for severe COVID-19 (age, sex, smoking, COVID-19 vaccination, history of COVID-19, body mass index (BMI), and comorbid conditions) was evaluated using univariate and multivariate analyses. Results: In total, 28,481 individuals were included, of whom 18,371 (64.5%) answered that they wore masks. After adjusting for confounders, older age (adjusted relative risk [RR], 1.50; 95% confidence interval [CI], 1.45–1.55 for “75–83” years), no history of COVID-19 (adjusted RR, 1.06; 95% CI, 1.04–1.08), low BMI (adjusted RR, 1.04; 95% CI, 1.02–1.07), and increased number of comorbid conditions (adjusted RR, 1.11; 95% CI, 1.05–1.18 for three or more) were significant positive factors for wearing a mask. In contrast, men (adjusted RR, 0.89; 95% CI, 0.87–0.90), no COVID-19 vaccination (adjusted RR, 0.78; 95% CI, 0.76–0.81), and current smoking history (adjusted RR, 0.96; 95% CI, 0.93–0.99) were significant negative factors. Conclusion: We demonstrated that mask-wearing behavior differed based on individual risk factors for severe COVID-19, with some risk factors negatively influencing mask use in Japan. It may be necessary to recommend mask-wearing for these individuals, especially during situations such as COVID-19 epidemic season or the onset of epidemics, considering individual mask-wearing behavior.